THE PSYCHOSOCIAL EFFECTS OF THE PROCESS OF RESOCIALIZATION OF THE TRANSSEXUAL BEING IN THE FRAMEWORK OF THE PRISON SYSTEM: A LITERATURE REVIEW - Raíra Alexandre, Andresa; Sousa Andreza, Raynara; Sousa Andreza, Raul (Health and Society, 2022)
This study aimed to analyze the psychosocial consequences of the process of resocialization of the transsexual individual in the face of the prison system. For this, a systematic literature review was carried out, the search for bibliographic material was carried out between March and April 2021 in the Scientific Electronic Library Online (Scielo) and Google academic databases. Applying the descriptors “Gender and prison”, a total of 16,412 studies was obtained. Following the exclusion criteria, articles whose publications were made between 2015 and 2019 were selected, with only those that had the full text used and that addressed topics related to the present study, excluding those that did not fit. Through the systematic analysis of the material, it was possible to observe the need for the psychologist’s work not only with the transgender convicts, but also with those who carry out the sentences, since they directly interfere in this rescue process. In addition, the importance of psychological assistance after prison is perceived, since the system scenario does not favor what is proposed as resocialization in addition to the impacts of how society sees transgender people, ex-prisoners.